Entre a coerção e a moralidade: por que as pessoas recolhem tributos? - Guilherme Andrade Carvalho (2018)
Since the French Revolution, with the transfer of economic activities to the private sector, taxes represent the main source of revenue for the states. If, on the one hand, the need for resources is intensified with increasing social spending, on the other, its collection is increasingly challenging. With the financialization of the economy and the mobilization of capital, states wage tax wars with seeking to attract investment, and tax evasion starts to represent a real threat to the subsistence of governments. The efficiency of tax collection is one of the main challenges to be faced in the contemporary world. It is therefore inevitable to analyze the reasons why people obey the laws, especially in the tax sphere. Exploring the theory developed by Frederick Schauer and the methodology of isolation of law, it is verified that people rarely obey the laws simply because they are inserted in the legal order. When legal dictates go against their personal interests and convictions, individuals tend to adopt a prudential rationale that takes into account the punishments and rewards resulting from acts of obedience or disobedience. In this scenario, coercion plays a prominent role in legal science and in providing prudential reasons for action. With the help of game theory, we sought to analyze the structure of the relations of strategic interactions between the tax authorities and their peers and the one existing between the tax authorities and the taxpayers, especially as regards the influence of coercion in the adoption of selfish or cooperatives. The research and results analyzed indicate that the sanction is not capable of individually explaining the volume of tax collection currently observed in the countries, since, from a purely economic and rational perspective, the payment of taxes rarely results in the best personal rewards. Faced with the complexity of human thinking, it was found that sanctions, although indispensable for modulation of behavior, interact with several other factors. Under the tax law, this set of reasons is called tax morality, which is influenced by several elements, especially social norms, equity and the relationship between players, especially the tax authorities and the taxpayer. In all of them it is possible to observe a strong influence of reciprocity among those involved. Respect between states and taxpayers, how these relationships are developed, and the way in which sanctions are applied directly influence voluntary compliance with tax obligations. The analysis and correct understanding of these elements can help in the construction of a more just, efficient and lasting tax system.